Política para inclusão de alunos com necessidades educacionais:um estudo em universidades e centro universitário de Santa Maria - RS - Castanho, Denise Molon (2007)
This study was carried out aiming at investigating the inclusion policies to students with special educational necessities in the Santa Maria RS universities and at the University Center in the same city. Higher Education constitutes a way to knowledge production and the University is the place where the values and practices of inclusive education should be lived. In this way, legislations and public policies must be considered in the implementation of the educational organizations actions because; the rights of students who have special educational necessities must be respected. The research presented was descriptive with case study characteristics and, with a qualitative approach. Interviews with gestors and students with special educational necessities were performed in the universities and at the University Center from Santa Maria - RS. Through the analysis one can infer that the inclusion of students with special educational necessities in the university is a recent discussion and, the presence of this student in this environment is new. While concluding, one can observe that the movements and advancements regarding the legislation are undeniable and, it is possible to notice among many questions that although embryonic the movements of the Santa Maria RS universities and from the University Center are being registered in the sense of producing ingression, access and retention of the student with special educational necessities. A lot must be done so that the universities as an educational institution give the opportunity and stimulate an education for all and, that the student with special educational necessities can have a life project concretized in society. The considered educational Institutions must be better prepared to a demand, which is increasing, of students with special educational necessities and, to do so they must stand up to political, economical and social scenery full of changes